Diagnostic Accuracy of 256-Detector Row Computed Tomography in Detection and Characterization of Incidental Pancreatic Cystic Lesions - D. Ippolito; P. Allegranza; P. A. Bonaffini; C. Talei Franzesi; F. Leone; S. Sironi (Gastroenterology Research and Practice)
Purpose. To assess the diagnostic value of 256-detector row MDCT in the characterization of incidentally detected pancreatic cystic lesions (PCLs). Materials and Methods. We retrospectively reviewed 6389 studies performed on a 256-row detector scanner, wherein ≥1 PCLs were incidentally detected. Images from a total of 192 patients (99 females; age range 31–90 years) were analysed referring to morphologic predictive signs of malignancy, including multifocality, inner septa, wall thickening, and mural enhancing nodules. Results. We evaluated 292 PCLs in 192 patients (solitary in 145 and ≥2 in 47; incidence 2.05%). Size ranged from 3 to 145 mm (mean 15 mm); body was the most common location (87/292; 29.8%). Intralesional septa were detected in 52/292 lesions (17.8%), wall thickening >2 mm in 13 (4.5%), enhancing wall and mural nodules in 15 (5.1%) and 12 (4.1%), respectively. Communication with ductal system was evident in 45 cases. The most common diagnoses, established by histology or imaging analysis, were IPMNs (about 86%), while serous cystic neoplasia (3.7%) and metastases (0.5%) were the less common. Conclusion. MDCT provides detailed features for characterization of PCLs, which are incidentally discovered with increased frequency due to the widespread use of cross-sectional imaging.